2014
DOI: 10.1007/s13353-013-0190-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial NADH dehydrogenase polymorphisms are associated with breast cancer in Poland

Abstract: Complex I NADH-oxidoreductase-ubiquinone transports reducing equivalents from the reduced form of NADH to ubiquinone (coenzyme Q-CoQ). The purpose of this study was to analyze mutations in MT-ND1, MT-ND2, MT-ND3 and MT-ND6 genes and their effect on the biochemical properties, structure and functioning of proteins in patients with breast tumours. In research materials, in 50 patients, 28 total polymorphisms and five mutations were detected. Most detected polymorphisms (50 %, 14/28) were observed in MT-ND2 gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…The differences in energy metabolism of tumour and normal cells are the biochemical basis for speculation about the therapeutic strategies, which in the future can be used for selective killing of tumour cells (5). Previous studies concerned mainly mutations in human mtDNA in carcinogenesis (7,11,12,34). Only a few authors have conducted investigations on the relationship between mutations and carcinogenesis process in dogs (3,22,28,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The differences in energy metabolism of tumour and normal cells are the biochemical basis for speculation about the therapeutic strategies, which in the future can be used for selective killing of tumour cells (5). Previous studies concerned mainly mutations in human mtDNA in carcinogenesis (7,11,12,34). Only a few authors have conducted investigations on the relationship between mutations and carcinogenesis process in dogs (3,22,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of mitochondrial DNA (mtDNA) sequences plays an important role in the studies on population genetics and in medicine, including veterinary medicine (7,11,12,(27)(28)(29)32). Results published in the recent years have indicated the prevalence of mitochondrial DNA mutations in tumour cells, which suggests that they may be cancer-causing agents (7,11,12,28,29,32,34).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Bai et al demonstrated the association of a nine-base pair deletion at nucleotide position 8272 (region V) of the mtDNA with postoperative survival rate in RCC [20]. In addition, mutations in NADH dehydrogenase subunit 1 ( ND1 ), a subunit of oxidative phosphorylation complex, were detected in breast and nasopharyngeal carcinomas [21,22]. Furthermore, Yusnita et al [23] identified 11 missense mutations in ND1 from colorectal tumor tissue specimens.…”
Section: Introductionmentioning
confidence: 99%